2022
DOI: 10.31219/osf.io/sgu25
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Test Use and Assessment Practices of School Psychology Training Programs: Findings from a 2020 Survey of U.S. Faculty

Abstract: The last comprehensive study to examine the assessment practices promoted by schoolpsychology programs was published 25 years ago (i.e., Wilson & Reschly, 1996). Since then,significant changes to assessment theory and practice have occurred. Data from a 2020 survey ofdirectors of school psychology programs were collected to gain an understanding of currentgraduate training in test use and assessment. Results were compared to a current survey ofpractitioners as well as past surveys of trainers. Results … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
(104 reference statements)
0
3
0
Order By: Relevance
“…The WJ IV ACH is an omnibus NRT of academic achievement that is commonly used by school psychologists (Benson et al, 2019) and school psychology trainees (Lockwood et al, 2022). The WJ IV ACH measures academic achievement in core curricular areas such as reading, writing, and mathematics, including five of the seven areas specified in the definition of specific learning disability (SLD) codified in the Individuals with Disabilities Education Act (IDEA, 2004).…”
Section: Importance Of Norm-referenced Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…The WJ IV ACH is an omnibus NRT of academic achievement that is commonly used by school psychologists (Benson et al, 2019) and school psychology trainees (Lockwood et al, 2022). The WJ IV ACH measures academic achievement in core curricular areas such as reading, writing, and mathematics, including five of the seven areas specified in the definition of specific learning disability (SLD) codified in the Individuals with Disabilities Education Act (IDEA, 2004).…”
Section: Importance Of Norm-referenced Testingmentioning
confidence: 99%
“…Benson et al’s 2017 survey of 1317 school psychologists (published in 2019) indicated that it is the third most frequently used omnibus NRT of academic achievement and is administered at least monthly by approximately 50% of school psychologists. Furthermore, a recent survey of 105 trainers of school psychologists by Lockwood et al (2022) found that the WJ IV ACH is the most commonly administered omnibus NRT of academic achievement by trainees, used in 87.3% of graduate programs.…”
Section: Importance Of Norm-referenced Testingmentioning
confidence: 99%
“…In school psychology, there is evidence that assessment training related to cognitive assessment includes instruction on low-value practices such as profile analysis, subtest analysis, and ipsative comparison (Lockwood & Farmer, 2020; Miller et al, 2020). Perhaps most troubling, a survey of trainers from 105 school psychology programs by Lockwood et al (2022) found that approximately 38% of programs require students to administer one or more projective test.…”
Section: Evidence-based Assessmentmentioning
confidence: 99%